Study on mechanism of low bioavailability of black tea theaflavins by using Caco-2 cell monolayer - Fengfeng Qu; Zeyi Ai; Shuyuan Liu; Haojie Zhang; Yuqiong Chen; Yaomin Wang; Dejiang Ni (Taylor & Francis Group, 2021)
This study aimed to clarify the bioavailability mechanism of theaflavins by using the Caco-2 monolayer in vitro model. Prior to the transport of theaflavin (TF), theaflavin-3-gallate (TF3G), theaflavin-3'-gallate (TF3'G), and theaflavin-3, 3'-digallate (TFDG), we found the cytotoxicity of theaflavins was in the order of TF3'G > TFDG > TF3G > TF, suggesting the galloyl moiety enhances the cytotoxicity of theaflavins. Meantime, the galloyl moiety made theaflavins unstable, with the stability in the order of TF > TFDG > TF3G/TF3'G. Four theaflavins showed poor bioavailability with the Papp values ranging from 0.44 × 10−7 to 3.64 × 10−7 cm/s in the absorptive transport. All the theaflavins showed an efflux ratio of over 1.24. And it is further confirmed that P-glycoprotein (P-gp), multidrug resistance associated proteins (MRPs) and breast cancer resistance protein (BCRP) were all shown to contribute to the efflux transport of four theaflavins, with P-gp playing the most important role, followed by MRPs and BCRP. Moreover, theaflavins increased the expression of P-gp, MRP1, MPR3, and BCRP while decreased the expression of MRP2 at the transcription and translation levels. Additionally, the gallated theaflavins were degraded into simple theaflavins and gallic acids when transported through Caco-2 monolayers. Overall, the structural instability, efflux transporters, and cell metabolism were all responsible for the low bioavailability of four theaflavins in Caco-2 monolayers.